50 brainstorming methods : for team and individual ideation - Curedale, Robert, ....- (Topanga : Design Community College, 2013)
When faced with a difficult problem, one of the best ways of finding an effective solution is to organize a brainstorming session. Brainstorming is a group ideation method that was popularized by Alex Faickney Osborn in the 1953 book Applied Imagination. Brainstorming remains today one of the most powerful methods available for developing original ideas. Brainstorming is a way of applying a collaborative approach to innovation. There are many different brainstorming methods. Different design practitioners can select different methods and apply them in different ways. You do not need to be an expert to participate in a brainstorm. The best results are obtained with a diverse team of participants which may include managers, designers, engineers, marketing, sales manufacturing professionals and end users of the product or service with people from different disciplines, cultures, gender, income and ages. This book includes methods with a variety of different approaches to brainstorming. I have included a number of warming up exercises which will help your participants produce productive outcomes quickly. Western organizations are turning to innovation as a primary way of differentiating their offering.
Includes index.
Keywords: Brainstorming